A novel, simple and rapid assay to measure citrate level in bacterial culture for analysis of citrate consumption by bacteria - Rattiyaporn Kanlaya; Chonnicha Subkod; Visith Thongboonkerd (Talanta Open)
Citrate is essential for Krebs cycle in eukaryotes and serves as a carbon source for some bacteria to survive/grow. Available methods for measuring citrate level rely mainly on enzymatic reactions and/or sophisticated instrumentations. This study aimed to develop a novel, simple and rapid assay to quantify citrate in bacterial culture for analysis of citrate consumption. The assay was initially tested with 0.1–25.6 mM citrate in deionized (dI) water or complete M9 medium without/with 0.25 M HCl. Wavelength scan revealed maximum absorption of citrate at λ210 nm with linear calibration curve (R2 = 0.9997–0.9999) when HCl was added. Among negatively charged chemicals tested, only oxalate interfered with the assay. After 24-h inoculation of Klebsiella pneumoniae (the known citrate-utilizing bacterium) in (20 mM) citrate-containing complete M9 medium, the remaining citrate significantly decreased (by 22.20±7.13 % consumption). However, a mild decrease was also observed in the sample without bacterial inoculation, suggesting that some components of the complete medium interfered with the assay. It was clearly evidenced that M9 salt, CaCl2 and/or MgSO4 were responsible for such interference. Finally, citrate at low concentrations (0.1–6.4 mM) in M9 medium with CaCl2 and/or MgSO4 provided the linear calibration curve (R2 = 0.9451–0.9986). At 5 mM, citrate consumption by K. pneumoniae after 24-h culture was 46.88±0.47 %. In summary, we have successfully developed a novel, simple and rapid method for measuring citrate level in bacterial culture. It will be very useful for measuring citrate consumption by typical and atypical citrate-utilizing bacteria for classification, mechanistic and pathophysiologic studies.